Effects of two fungicide formulations on microbial and macroinvertebrate leaf decomposition under laboratory conditions. (28th June 2016) - Elskus, Adria A.; Smalling, Kelly L.; Hladik, Michelle L.; Kuivila, Kathryn M.
Abstract: Aquatic fungi contribute significantly to the decomposition of leaves in streams, a key ecosystem service. Little is known, however, about the effects of fungicides on aquatic fungi and macroinvertebrates involved with leaf decomposition. Red maple ( Acer rubrum ) leaves were conditioned in a stream to acquire microbes (bacteria and fungi) or leached in tap water (unconditioned) to simulate potential reduction of microbial biomass by fungicides. Conditioned leaves were exposed to fungicide formulations QUILT (azoxystrobin + propiconazole) or PRISTINE (boscalid + pyraclostrobin) in the presence and absence of the leaf shredder, Hyalella azteca (amphipods; 7‐d old at start of exposures) for 14 d at 23 °C. The QUILT formulations (∼0.3 μg/L, 1.8 μg/L, and 8 μg/L) tended to increase leaf decomposition by amphipods (not significant) without a concomitant increase in amphipod biomass, indicating potential increased consumption of leaves with reduced nutritional value. The PRISTINE formulation (∼33 μg/L) significantly reduced amphipod growth and biomass ( p < 0.05), effects similar to those observed with unconditioned controls. The significant suppressive effects of PRISTINE on amphipod growth and the trend toward increased leaf decomposition with increasing QUILT concentration indicate the potential for altered leaf decay in streams exposed to fungicides. Further work is needed to evaluate fungicide effects on leaf decomposition under conditions relevant to stream ecosystems, including temperature shifts and pulsed exposures to pesticide mixtures. Environ Toxicol Chem 2016;35:2834–2844. Published 2016 Wiley Periodicals Inc. on behalf of SETAC. This article is a US Government work and, as such, is in the public domain in the United States of America.